Transcriptome Analysis of Crassostrea sikamea (♀) × Crassostrea gigas (♂) Hybrids Under Hypoxia in Occluded Water - Zhang, Xuekai; Fan, Chao; Li, Jinlong; Zhang, Xingzhi; Li, Qiongzhen; Wang, Zhaoping (Frontiers in Marine Science, 2022)
Hypoxia is considered to be one of the key factors affecting the survival of sea animals, it is necessary to parse the molecular processes involved in the response to hypoxia. As a potential selectively breed species, the hybrid of Crassostrea sikamea (♀) × C. gigas (♂) shows valuable heterosis in survival and growth traits. Thus, RNA de novo was deployed in this study to analyze the molecular processes in the hybrids under hypoxia stress. The hybrids were cultured in an occluded water, then the dissolved oxygen was gradually consumed by oysters, and the gill tissue of hybrids were sampled at very beginning and the lowest respiration point in the experiment. In the current study, 901 significant differentially expressed genes (DEGs) were identified under hypoxia compared to normoxia, among which 432 DEGs were downregulated, and the other 469 DEGs were upregulated. 27 GO terms were significantly enriched, such as integral component of membrane, extracellular region, immune response, tumor necrosis factor receptor binding, and neurotransmitter: sodium symporter activity, etc. Besides, 19 KEGG pathways were significantly enriched, like Apoptosis, Th1 and Th2 cell differentiation, Complement and coagulation cascades, Antigen processing and presentation, Notch signaling pathway, and Cytokine-cytokine receptor interaction, etc. The current analysis showed that the HSP70 and TRAIL genes were downregulated, but the LIGHT genes were upregulated, which indicated the inhibited of Apoptosis, and the activity of innate immunity in oysters under hypoxia. This study provides preliminary insight into the molecular response of hybrids to hypoxia and understand of the oyster hybrid breeding.